La construction d'un partenariat éducatif. Sociohistoire d'un dispositif de lutte contre le décrochage scolaire - Alicia Jacquot
This article examines the conditions for setting up an anti-dropout program in middle school - the "atelier relais" - as well as the partnership at work in the articulation of the two distinct social worlds of popular education and national education. The first part of the project traces the intersecting history of these two worlds, based on archives and memorial interviews. The second part analyzes the speeches of the institutional actors of this system (national associative leaders and National Education leaders). It reveals the existence of similar